Persepsi Siswa Laki-Laki Terhadap Pembelajaran Seni Tari Di SMP Negeri 5 Padang - Yunia Dwi Safitri; Marzam Marzam (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to see and describe male students' perceptions of dance learning at SMP Negeri 5 Padang. This type of research is quantitative descriptive research. This research instrument is the researcher himself and is assisted by supporting instruments in the form of Likert scores. Data collection techniques are questionnaires, observations, interviews and documentation. The data were analyzed using descriptive statistical techniques. The results of this study show that male students' perception of dance learning is categorized as low because male students think that dancing is only for female students because according to them dance movements are only vigorous movements. Male students' perception of dance learning at SMP Negeri 5 Padang based on interest indicators is categorized as low with a percentage of 59.33%, attention indicators are categorized as low with a percentage of 59.00%, mood indicators are categorized as low with a percentage of 57.33%, physiological indicators are categorized as low with a percentage of 58.07%, need indicators are categorized low with a percentage of 56.00%, stimulus indicators are categorized low with a percentage of 66.13%, and environmental indicators are categorized as low with a percentage of 62.67%. For overall, male students' perception of dance learning at SMP Negeri 5 Padang is categorized as low with a total percentage of 59.02%.